TECHNO-ECONOMIC STUDY OF COCONUT HUSKS DECOMPOSING MACHINE FOR FARMER GROUP SCALE - Tooy, Dedie; Lantang, Dewinta; Rantung, Ruland Aswin; Rumambi, David P; Longdong, Ireine Adriana; Pinatik, Herry Frits (ITScience (Information Technology and Science), 2023)
Many coconut husks in coconut-producing área have not been maximally utilized, especially on a small scale for farmers. It happened due to the difficulty of obtaining simple small-scale coconut decomposing machines, and the region must import it from other regions. As a result, the utilization of coconut fiber in fiber and cocopeat is still minimal. Plus, when bringing in from outside, the logistics cost of the coconut husk decomposing machine is still high. This research aims to conduct a techno-economic analysis of a small-scale coconut husk decomposer from the machine designed and made. The research method was using the experimental method. The results showed that the equipment can produce cocofiber and cocopeat with 600 kg of husk per day for 6 hours of use. The results of economic calculations based on the IRR value, the net B/C ratio, and the payback period show that this machine is feasible to be developed on a small scale for Farmer groups. Technologically, this machine is simple and relatively easy to operate. Further research hopes this machine will prove its durability over long, heavy work periods.